Al-hajjah Tunazzal Manzilah Al-dharurah In Prevention Venous Thromoembolism (VTE) During Pregnancy And Puerperium - Irwan Mohd Subri; Nur Zaireena Zainal; Azman Ab. Rahman; Mohd Nasir Abd Majid; Nadeeya'ayn Umaisara Mohamad Nor; Zizi Azlinda Mohd Yusof; Amir Husin Mohd Noor; Fitriah Wardi (Centro de Investigaciones en Ciencias Sociales y Humanidades desde America Latina, 2024)
Fatwa on Clexane and Fraxiparine which are used for Venous Thromboembolism (VTE) during pregnancy and puerperium, imposed by the Malaysian National Fatwa Council (MNFC) in 2009 stating that both types of low molecular weight heparin (LMWH) is prohibited except in darurah only due to its porcine preparation ground. Thus, this paper embarks to expound to which extent unlawful sources for medical prevention and treatment can be used for Muslim consumption. Is it only when a darurah condition is announced as an exemption situation that the intoxicating material is allowed in medicine? This research employs qualitative methodology using document review method to analyse the content of the document including medical journals and Shariah books. Observing the alarming maternal mortality due to VTE during pregnancy and puerperium in Malaysia nowadays, it is true that VTE is a fatal and life threatening illness. Due to that, LMWH is recommended by the Ministry Health of Malaysia (MOH). With LMWH features of accessibility, feasibility, effective and safety profile, it becomes the first line of option among O&G doctors in Malaysia albeit it is porcine based. Therefore, this paper found that the prevention of VTE using LMWH when diagnosed as a moderate risk during pregnancy and low risk during puerperium is allowed in the shariah perspective based on Islamic legal maxim namely Al-Hajah Tunazzal Manzilah Darurah.